Development of Performance Assessment Instrument for Electrolyte and Non Electrolyte Solutions - Sahara, Besta Rosita; Kadaritna, Nina; Tania, Lisa (Jurnal Pendidikan MIPA, 2019)
This study was aimed to develop the performance assesment instrument on the practice of electrolyte and non-electrolyte solution, to describe the characteristics in terms of legibility, construction, implementation of product, and to describe the teachers responses on the performance of developed. The design of this research was Research and Development (R&D). The result of expert validation toward assessment instrument showed the level readable realibility, construction, and implementation of the performance assesment instrument equal to 91,11%, 84%, and 100%; respectively. The teachers gave very good responses to the legibility content, construction, and implementation of the performance assesment instrument with percentage were 96,67%, 96%, and 96,67% respectively. The conclusion obtained from this research is the performance of developed were excellent.Keywords: assessment performance instrument on experiment, electrolyte solution development. DOI: http://dx.doi.org/10.23960/jpmipa/v20i1.pp23-29